2000
DOI: 10.1086/317054
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength Examination of theCOS BField 2CG 075+00 Yields a Blazar Identification for 3EG J2016+3657

Abstract: We present a high-energy study of the intriguing COS-B γ-ray field, 2CG 075+00, in order to search for possible counterparts. New EGRET data show that the COS-B emission probably corresponds to two localized γ-ray sources, 3EG J2016+3657 and 3EG J2021+3716. Spectral fits to these EGRET sources, assuming a power-law model, yield photon indices of ∼ 2 for each object. We examine archival ROSAT and ASCA X-ray data which overlap both EGRET error boxes, and find several point sources in the region to a flux limit o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 43 publications
(44 reference statements)
6
51
0
Order By: Relevance
“…Often additional information from observations at other wave bands is used to aid in the identification of the EGRET sources. Progress has been made with recent studies in the X-ray band carried out for several EGRET fields (e.g., Roberts, Rowani, & Kawai 2001) and used to suggest counterparts for a few unidentified EGRET sources, such as 3EG J2227+6122 (Halpern et al 2001a), 3EG J1835+5918 (Mirabal et al 2000;Mirabal & Halpern 2001;Reimer et al 2001), and 3EG J2016+2657 (Mukherjee et al 2000;Halpern et al 2001b).…”
Section: Introductionmentioning
confidence: 99%
“…Often additional information from observations at other wave bands is used to aid in the identification of the EGRET sources. Progress has been made with recent studies in the X-ray band carried out for several EGRET fields (e.g., Roberts, Rowani, & Kawai 2001) and used to suggest counterparts for a few unidentified EGRET sources, such as 3EG J2227+6122 (Halpern et al 2001a), 3EG J1835+5918 (Mirabal et al 2000;Mirabal & Halpern 2001;Reimer et al 2001), and 3EG J2016+2657 (Mukherjee et al 2000;Halpern et al 2001b).…”
Section: Introductionmentioning
confidence: 99%
“…3EG J2016+3657 was identified in a detailed study that was carried out on archival X-ray data, with follow-up optical observations of the γ-ray error box (Mukherjee et al 2000). The identification was soon confirmed by Halpern et al (2001), who concluded that B2013+370 was the most likely counterpart, after optical spectroscopic identifications of all the soft and hard X-ray sources in the error circle of the EGRET source eliminated the other candidates.…”
Section: A Blazar Counterpart For 3eg J2016+3657mentioning
confidence: 97%
“…In fact 2CG 078+2 (3EG J2020+4017) was thought to be a counterpart of the supernova remnant (SNR) γ-Cygni. Multiwavelength measurements were used to identify counterparts of 3EG J2016+3657 (Mukherjee et al 2000;Halpern et al 2001) and of 3EG J2020+4017 (Becker et al 2004;Weisskopf et al 2006;Bykov et al 2004Bykov et al , 2006 with some success.…”
Section: Introductionmentioning
confidence: 99%
“…The location of MGRO J2019+37 is consistent with those of the EGRET sources 3EG J2016+3657 and 3EG J2021+3716. The first of them is positionally coincident with the blazar-like source B2013+370 (G74.87+1.22) (Mukherjee et al 2000;Halpern et al 2001), although this blazar is well outside the inner box of MGRO J2019+37. The second is marginally coincident with the pulsar wind nebula PWN G75.2+0.1 (Hessels et al 2004).…”
Section: Observationsmentioning
confidence: 98%